Deep vein thrombosis and pulmonary embolism in the military patient. Issue 3 (5th August 2015) - Bauld, Richard A; Patterson, C; Naylor, J; Rooms, M; Bell, D
Abstract : Objectives: Venous thromboembolism (VTE), encompassing deep vein thrombosis and pulmonary embolism, is a common, potentially lethal condition and a cause of long-term morbidity and functional limitation. This paper is a clinical review focused on military epidemiology, evidence-based recommendations for prevention, diagnosis and management of VTE and occupational considerations in a military population. Methods: A literature review was conducted through Pubmed and Embase for systematic reviews, meta-analyses and clinical trials relating to VTE. Guidelines from the National Institute for Health and Care Excellence, British Thoracic Society and the American College of Chest Physicians were reviewed and recommendations considered. Results: Acute morbidity from VTE can range from limb pain and swelling to life-threatening cardiovascular compromise. Long-term sequelae include postthrombotic syndrome, chronic thrombosis and pulmonary hypertension. Diagnosis should follow a validated pathway depending on the patient's prerest probability. The management of the condition should vary with attention to risk stratification. Discussion: Prompt initiation of anticoagulation reduces symptoms, rates of recurrent VTE and death but treatment must be balanced against the risk of major haemorrhage. Military operations expose personnel to a unique combination of risk factors for VTE and operating in austere environments can increase the challenge of diagnosis, prognostication and management. Furthermore, there are implications for troop attrition, operational readiness and return to work.